Civic Values in Action: Integrating Pancasila and Local Wisdom into Digital Citizenship - Sri Rejeki; Wahyu Azwar; Rihal Jayadi; Aliahardi Winata; Isnaini Isnaini; Malami Muhammad Garba (Al-Qalam Institue, 2026)
This study aims to analyze the integration of Pancasila values and local wisdom into digital citizenship, identify their application in concrete actions within the digital space, and formulate a value-based conceptual model of digital citizenship relevant to digital dynamics that need to be managed and addressed through digital literacy to foster responsible citizenship in social media use. This study employs a Systematic Literature Review (SLR) method by examining 40 scientific articles published between 2016 and 2026, indexed in the Google Scholar and Scopus databases. Data were collected through documentation using Mendeley and systematically analyzed to identify patterns, concepts, and research findings. The results indicate that the integration of Pancasila values and local wisdom plays a strategic role in shaping students’ character in the digital age. Conceptually, Pancasila serves as a normative foundation, while local wisdom provides contextual relevance within the socio-cultural context. Practically, this integration is implemented through an action-oriented citizenship model, encouraging students to actualize these values in their daily digital behaviors. The implications of this study highlight the importance of strengthening value-based digital citizenship to develop responsible, critical, and ethical digital citizens.